Stability of Silver Nanoparticles as Imaging Materials - Umi Nur Sholikhah; Anung Pujiyanto; Enny Lestari; Endang Sarmini; Triani Widyaningrum; Kadarisman Kadarisman; Triyanto Triyanto; Putri Puspitasari (The Journal of Pure and Applied Chemistry Research, 2016)
Determining the stability of silver nanoparticles is a very important process. It was associated with unwanted metal charge and materials properties. Therefore, we studied to synthesis and stability of silver nanoparticles (AgNPs). The synthesis was performed by reduction method used sodium borohydride (NaBH4). Silver nitrate solution 0.0005 M in 1 mL was reduced using 1 mL 0.002 M of NaBH4. Then a 40.0 mL of polyvinylpyrrolidone 0.3% and 20 mL of 1.5 N NaCl was added to the mixture. Characterization of silver nanoparticles is undertaken using spectrophotometer UV-Vis, transmission electron microscopy, particle size analyzer and zeta potential. The stability of products is observed for 5 times using spectrophotometer UV-Vis. The product was characterized by determining its surface plasmon resonance (SPR) of AgNPs and the result was obtained at 403 nm. The size of AgNPs was 20 nm using tomography emission microscopy analysis and the particle size distribution give 5.8 nm. The dielectric charge was 53 mV. The stable AgNPs showed no significant SPR shift at 402±0.89 nm wavelength during 5 days observation. Based on the size and stability, it was suitable for imaging materials.